Assessment of Reinforcement Effect of FRP-Strengthened Shield Segment Joint Based on the CZM Model - Jianjun Kuang; Yuanqing Chen; Xiaofei Li; Wei Guo; Jia Li; Yiqun Huang (Advances in Civil Engineering)
As the weakest link in the shield segment, the reinforcement and repair technology of shield segment joint has received widespread attention. In this study, an finite element model utilizing a cohesive zone model (CZM) was constructed to simulate the mechanical behavior of the shield segment joint during the whole fracture process. The proposed modeling method of joint allows multiple layers of steel bars to be stacked without interference by applying cohesive elements. Cohesive elements were employed to represent the mechanical response of potential fracture surfaces in concrete, as well as the interfaces between steel–concrete and fiber-reinforced polymer (FRP)–concrete, by utilizing various constitutive models tailored for mixed-mode loading conditions. A group of experiments was chosen to assess the precision of the proposed model by comparing the mechanical response and the fracture patterns. Finally, parameter analyses were conducted to study the reinforcement effect of the FRP bonding length and width on the shield segment joint. The results indicate that external bonding of FRP can effectively enhance the bearing capacity and stiffness of shield segment joints. However, insufficient bonding length or width may significantly reduce the strengthening effect and potentially decrease the ductility of the joint.